Akademik W. M. Monachow - niezwykły człowiek, uczony, dydaktyk i organizator nauki - Utiejewa, Roza A.; Pardała, Antoni (Annales Universitatis Paedagogicae Cracoviensis | Studia ad Didacticam Mathematicae Pertinentia, 2017)
The authors refer to the atmosphere, the issues and the results of this year international conference in Togliatti ’2010 dedicated to 75 years of the academician W. M. Monachow. The authors remind his way to creative development of didactics subjects and educational technology and point out and analyze his selected achievements. In particular, they express gratitude to himself, his collaborators and supervisors for support and scientific cooperation with Poland in the field of education of mathematics and physics researchers and educators.